Деформирование и долговременная повреждаемость зернистых композитных материалов при температурных воздействиях - Хорошун, Л.П.; Шикула, Е.Н. (Прикладная механика, 2010)
A theory of long-term damageability is suggested for the granular composite materials with allowance for temperature effect. The process of damage of composite components is modeled by forming the stochastically arranged micropores. A criterion of destruction of unit microvolume is characterized by its long-term strength, which is described by dependence of brittle fracture duration on the degree of closeness of equivalent stress to its limit value. The last characterizes the short-time damage by Schleicher-Nadai criterion, which is assumed to be the stochastic function of coordinates. For arbitrary moment, the equation for balance of damage (porosity) of components with allowance for temperature constituent is formulated. The algorithms is built for evaluation of dependences of microdamage of granular material components, microstresses on time. The corresponding curves are obtained. An effect of temperature on curves of macrodeformation and damage of material is studied.